ASSESSMENT OF PROBLEMS ASSOCIATED WITH POLYTHENE WASTE DISPOSAL IN POMPOMARI WARD, DAMATURU LOCAL GOVERNMENT AREA YOBE STATE NIGERIA - Mohammed, Umar Mustapha; Isa, Mohammed (FUDMA Journal of Sciences, 2025)
The study investigates the impact of polythene waste disposal in Pompomari ward, Damaturu. Polythene waste poses a significant environmental challenge in the urban areas of Yobe State. Today one noticeable trend in Nigerian urban settings in recent years is the gradual takeover of almost every available open space by polythene waste. A total number 60 questionnaires were distributed randomly, aiming to capture the perspectives and experiences of a diverse group of respondents. The data collected were analyzed using descriptive statistics for each research questions. The result of the study revealed among others that; poor solid waste disposal lead to outbreak of diseases as the result shows that majority of the respondent were of the view that poor solid waste disposal lead to outbreak of diseases. It is evident that issues such as inadequate recycling facilities (33.33%), limited awareness (25%), regulatory enforcement (16.67%), and environmental indifference (20%) need immediate attention to establish a solid foundation for informed waste management decisions. The study recommended among others that the community leaders of the ward should be encouraged to enlighten people on the dangers associated with poor solid waste disposal through the public enlightenment to stop dumping of solid waste indiscriminately particularly polythene as this may help to reduce the outbreak of diseases. The study finding also showed that, the majority of the residents practiced improper solid waste management.